Establishing a three-step model of designing the polling stations for shorter queue and smaller waiting time: a case study using computer simulation. Issue 4 (2nd October 2017) - Au, Cheuk Hang; Xu, Zewen; Wang, Lin; Fung, Walter S.L.
ABSTRACT: This article tries to address the issue of lengthy queues at the polling stations during elections using simulation. It is known that the long queues may harm the voting experience and turn voters away. Moreover, the queuing problems have been repeating in different countries. We tried to use computer simulation to address this problem, with a polling station in the 2016 Hong Kong Legislative Election as the study target. We found and addressed the bottlenecks of the station successfully by reallocating the resources in the polling station in the simulations. Based on our results, we establish a three-step model for shortening the polling stations queues and waiting time more generally.